«Il posto del paesaggio» nella poesia di Antonella Anedda (TEST Ticontre. Theory Text Translation, 2026)
The present article seeks to provide a reconstruction of the forms and functions of landscape, understood as relational space, as it appears in Antonella Anedda’s poetry. The objective of this study is to demonstrate the pivotal function of prior literary and figurative references in the ostensibly immediate depiction of the encounter between a subject and a segment of nature in poetic compositions. This article focuses in particular on two texts, Paesaggio (Dal balcone del corpo) and Esilii (Historiae), which illustrate how meditation on death, the body and identity falls variously within the orbit of the discourse on Anedda’s landscapes.